2020
DOI: 10.1038/s41419-019-2211-z
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Protease Nexin I is a feedback regulator of EGF/ PKC/MAPK/EGR1 signaling in breast cancer cells metastasis and stemness

Abstract: An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Both EGF and its receptor partake in the pathogenesis of multiple carcinomas, thus constituting attractive targets for molecular therapy. Previous studies have demonstrated that EGF and EGFR are implicated in the invasion and migration of thyroid tumors, and that PN-1 can form a positive feedback with EGF/EGFR signaling to promote the biological activity of breast cancer cells (11)(12)(13). Therefore, the present study aimed to explore whether SERPINE2 could form positive feedback signals with EGF/EGFR, and participate in the proliferation, invasion and migration of papillary thyroid carcinoma.…”
Section: Introductionmentioning
confidence: 95%
“…Both EGF and its receptor partake in the pathogenesis of multiple carcinomas, thus constituting attractive targets for molecular therapy. Previous studies have demonstrated that EGF and EGFR are implicated in the invasion and migration of thyroid tumors, and that PN-1 can form a positive feedback with EGF/EGFR signaling to promote the biological activity of breast cancer cells (11)(12)(13). Therefore, the present study aimed to explore whether SERPINE2 could form positive feedback signals with EGF/EGFR, and participate in the proliferation, invasion and migration of papillary thyroid carcinoma.…”
Section: Introductionmentioning
confidence: 95%